Medicinal plants and their validation challenges in traditional Egyptian medicine - Heba M. Amer, Ayman A. Mohammad (Journal of Applied Pharmaceutical Science, 2022)
Remediation with medicinal herbal drugs is used in almost all cultures. Recently, herbal medicine has gained growing popularity in the current medical practice. The herbal products are considered available, acceptable, cheap, and safe products; thus, there is confidence in using these products. So, the quality, efficiency, and safety assurance of plant medicines became critical issues in both developed and developing countries. By standardizing the plant-derived drugs, a new era of a future remedy and healthcare system could be created. In order to keep this knowledge, historical records of medicinal plants are needed to be used for the benefit of humanity before their extinction forever. Egypt is characterized by a unique aromatic and medicinal flora that is required in the global market, which could increase the Egyptian exports. But there are several obstacles to the competition of Egyptian aromatic plants in the world market. Therefore, this review describes the historical use of medicinal plants throughout the published data using online search engines. The recent challenges in the quality, efficacy, authenticity, toxicity, and consistency of medicinal plants will be discussed. Also, this review aims to explore the economic situation and challenges of the herbal medicine industry in Egypt.
Keywords: Traditional medicine, authenticity, challenges, phytoconstituents, drug discovery